Wnt/β-catenin pathway activation is associated with glucocorticoid secretion in adrenocortical carcinoma, but not directly with immune cell infiltration - Maier, Tanja; Landwehr, Laura-Sophie; Triebig, Alexandra; Kircher, Stefan; Schauer, Marc P.; Knösel, Thomas; Sbiera, Silviu; Schwarzlmueller, Paul; Zimmermann, Petra; Reincke, Martin; Weigand, Isabel; Fassnacht, Martin; et al. (Frontiers in Endocrinology, 2025)
BackgroundIn advanced adrenocortical carcinoma (ACC), the response rate to immune checkpoint inhibition (ICI) is only ~15%. Glucocorticoid (GC) secretion and the activation of the Wnt/β-catenin pathway have been suggested to contribute to low tumour immune cell infiltration. The transcription factor lymphoid enhancer factor 1 (LEF-1) transduces β-catenin (CTNNB1)-mediated transcriptional activation.ObjectiveTo understand the contribution of Wnt/β-catenin pathway activation and glucocorticoid receptor (GR) signalling to the immunologically cold ACC tumour microenvironment.MethodsSemi-quantitative immunohistochemistry (IHC) of β-catenin (CTNNB1), LEF-1, GR and T cell markers CD3, CD4, CD8, Fox P3 in 59 ACC samples. Targeted RNA expression analysis of 354 immune-related genes in 58 additional ACC tissue specimens. Correlative analyses with clinical data.ResultsNuclear LEF-1 and CTNNB1 protein expression were positively correlated in ACC tissue (Pearson R2 = 0.1283, p=0.0046). High, moderate and low protein expression was detected in 24.1%, 53.2% and 19.3% of samples for LEF-1, and 30.6%, 43.5% and 19.3% for CTNNB1, respectively. We found higher LEF-1 expression in GC-secreting tumours which did not differ from inactive tumours in terms of GR expression. T cell markers, as evaluated by IHC, were not associated with expression of Wnt/β-catenin pathway markers. At RNA level, tumours with high LEF-1 expression showed significant downregulation of 37 transcripts (including 8 involved in antigen presentation). High LEF-1 expression levels correlated with worse overall survival in this cohort. This was not the case for CTNNB1 and GR.ConclusionLef-1 expression is useful as a biomarker of activated Wnt/β-catenin signalling in ACC. Wnt/β-catenin pathway activation was not associated with reduced immune cell markers in ACC but GC secretion and may be related to tumoural antigen presentation.